A high gain aperture match parabolic horn antenna with stable phase center and higher FBR in S‐band - Baghel, Amit Kumar; Kulkarni, Shashank Satish; Nayak, Sisir Kumar (Microwave and optical technology letters, 2021)
This paper presents an aperture matched parabolic pyramid horn antenna (APPHA) having flaring in the E‐ and H‐ plane. The proposed structure is designed and manufactured for S‐band (2.2–3.3 GHz) with a semicircular aperture matched section in both planes. The APPHA gives half power beam width (HPBW) less than 17° and 15° in the E‐ and H‐ planes, respectively due to the parabolic profile and aperture match section. An average improvement in front to back ratio and gain is 18.53 dB and 1.45 dBi, respectively compared to the conventional pyramidal horn antenna. The maximum variation in the phase center is also 2.8 cm. The measured return loss and cross‐polarization of less than 12 and 20 dB, respectively, is seen throughout the band, thus providing a good impedance matching. The proposed antenna having higher gain and lower HPBW can be used for wireless power transfer applications due to point directive beam to charge the batteries of quad‐copter, sensors as well as being a good candidate for parabolic dish reflector feed.